Learning Transformation Through Digital Leadership: A Case Study of SMPN 8 Toboali, South Bangka - Desi, Desi Ari; Suyatno, Suyatno; Zuhaery, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to explore how the principal’s digital leadership transforms learning at SMP Negeri 8 Toboali, South Bangka. Using a qualitative approach with an intrinsic case study design, the research employed in-depth interviews, participatory observations, and documentation involving the principal, two teachers, and two students. The findings reveal that the principal established a well-defined digital vision, fostered a participatory digital learning culture, and designed professional development strategies that enable teachers to adapt to emerging technologies. Digital-based managerial communication and the strategic use of social media strengthened transparent and collaborative school governance. The study also shows an increase in students’ learning motivation through the integration of digital media, along with the emergence of various local solutions to address infrastructural limitations. Overall, visionary, participatory, and responsive digital leadership serves as a key catalyst in driving learning transformation within educational institutions located in non-urban areas.